Baseline circulating IL-17 predicts toxicity while TGF-β1 and IL-10 are prognostic of relapse in ipilimumab neoadjuvant therapy of melanoma. Issue 1 (15th September 2015) - Tarhini, Ahmad A.; Zahoor, Haris; Lin, Yan; Malhotra, Usha; Sander, Cindy; Butterfield, Lisa H.; Kirkwood, John M.
Abstract : Background: We evaluated candidate circulating serum cytokines, chemokines and growth factors in patients with locally/regionally advanced melanoma receiving neoadjuvant ipilimumab with toxicity and clinical outcome. Methods: Patients were treated with ipilimumab (10 mg/kg IV every 3 weeks, 2 doses) before and after surgery. xMAP multiplex serum testing for 36 functionally selected cytokines and chemokines was performed at baseline and at six weeks (following ipilimumab). Based on our prior data, the association of IL-17 and immune related colitis was tested. Serum cytokines were divided into functional groups (Th1, Th2, Regulatory, Proinflammatory) and were assessed at baseline and week 6 using sparse-group Lasso modeling to assess the association of various cytokine groups with progression free survival (PFS). The linear combination of the cytokines/chemokines in this model was then used as a risk score and a Kaplan-Meier curve was generated to examine the association of the dichotomized score and PFS. Results: Thirty-five patients were enrolled whose staging was: IIIB (3; N2b), IIIC (30; N2c, N3), IV (2). Median follow-up was 18 months. Among 33 evaluable patients, median PFS was 11 months (95 % CI = 6.2–19.2). IL-17 was found to correlate significantly with the incidence of grade 3 diarrhea/colitis when measured at baseline ( p = 0.02) with a trend towards significance at 6 weeks ( p = 0.06). In the modeling analysis, at baseline, the linear combination of 2 regulatory cytokines [TGF- β1 ( ρ = 0.19) and IL-10 ( ρ = -0.34)] was significantly associated with PFS (HR 2.66; p = 0.035). No significant correlations with clinical outcomes were found in examining the week 6 cytokines. Conclusions: Baseline IL-17 level was significantly associated with the later development of severe diarrhea/colitis while the combination of baseline TGF- β1 and IL-10 levels were associated with therapeutic clinical outcome after neoadjuvant ipilimumab. These findings warrant further investigation and validation. Trial registration: ClinicalTrials.gov Identifier NCT00972933 .